Forty years after: reconsidering the problem of Descartes’s Natural Institution theory vs the Coextension theory - Сепетий, Дмитро Петрович; Sepetyi, Dmytro (My University, 2019)
The article discusses Margaret Wilson’s argument to the point that Descartes’s account of the mind-body interaction is incoherent because it involves two conflicting theories, the Natural institution theory and the Coextension theory, and later treatments of the problem by Marleen Rozemond, Minna Koivuniemi, and Edmond Curley. The first section deals with Wilson’s suggestion that Descartes’s Natural Institution theory conflicts with his statement that sensations arise from the soul-body union. The case is made that the suggestion is likely to be mistaken, and that the simplest way to reconcile the theory and the statement is to consider the union as an enduring dispositional relationship that is a precondition for particular interactions and their effects. The second section examines Marleen Rozemond’s alternative explanation of how the union is supposed to explain interactions and the qualitative character of sensations; it is argued that this account fails to provide a genuine tenable alternative to what Rozemond calls ‘interactionism’. The third section discusses the recent article by Koivuniemi and Curley, which answers Wilson’s second worry about the coherence of Descartes’s views on the union. The author also points out and explains away the seeming discrepancy between Koivuniemi’s and Curley’s account of the union, insofar as it treats the body-to-mind and mind-to-body directions of interaction symmetrically, and Wilson’s and Rozemond’s accounts, insofar as they involve a marked asymmetry in favour of the body-to-mind direction.
Keywords: Descartes; mind; body; union; interaction; Natural Institution; coextension